2001
DOI: 10.1021/ac010552f
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Instrument for Measuring Atmospheric NO2

Abstract: We report on the development of a high-sensitivity detection system for measuring atmospheric NO2 using a laser-induced fluorescence (LIF) technique around 440 nm. A tunable broad-band optical parametric oscillator laser pumped by the third harmonic of a Nd:YAG laser is used as a fluorescence excitation source. The laser wavelength is tuned at peak and bottom wavelengths around 440 nm alternatively, and the difference signal at the two wavelengths is used to extract the NO2 concentration. This procedure can gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Reduction of NO 2 to NO using a heated molybdenum catalyst or a photolytic converter followed by detecting the chemiluminescence of the reaction of NO with O 3 is the most common method (Kley and McFarland, 1980;Ryerson et al, 2000). Long path differential optical absorption (Platt et al, 1979), diode laser based absorption (Lenth and Gehrtz, 1985;Sonnenfroh and Allen, 1996;Li et al, 2004) and fluorescence (Thornton et al, 2000;Matsumoto et al, 2001;Matsumi et al, 2001;Dari-Salisburgo et al, 2009) spectroscopy are approaches to detect NO 2 directly. During the last decade cavity ring-down spectroscopy (CRDS) and its related forms cavity enhanced absorption spectroscopy (CEAS) and cavity attenuated phase shift spectroscopy (CAPS) have become powerful techniques to detect atmospheric trace gases (Ball and Jones, 2003;Brown, 2003) and have also been applied to NO 2 detection.…”
Section: Intercomparison Saphirmentioning
confidence: 99%
“…Reduction of NO 2 to NO using a heated molybdenum catalyst or a photolytic converter followed by detecting the chemiluminescence of the reaction of NO with O 3 is the most common method (Kley and McFarland, 1980;Ryerson et al, 2000). Long path differential optical absorption (Platt et al, 1979), diode laser based absorption (Lenth and Gehrtz, 1985;Sonnenfroh and Allen, 1996;Li et al, 2004) and fluorescence (Thornton et al, 2000;Matsumoto et al, 2001;Matsumi et al, 2001;Dari-Salisburgo et al, 2009) spectroscopy are approaches to detect NO 2 directly. During the last decade cavity ring-down spectroscopy (CRDS) and its related forms cavity enhanced absorption spectroscopy (CEAS) and cavity attenuated phase shift spectroscopy (CAPS) have become powerful techniques to detect atmospheric trace gases (Ball and Jones, 2003;Brown, 2003) and have also been applied to NO 2 detection.…”
Section: Intercomparison Saphirmentioning
confidence: 99%
“…Comparisons of the LIF-based NO 2 instruments to PF-CL instruments have also been described by Matsumoto et al (2001) and by Matsumi et al (2001). The comparison of all data points NO 2 = 0-6 ppb described by Matsumoto et al in the marine boundary layer in Okinawa Island, Japan, showed agreement to within 2% with an R 2 of 0.99.…”
Section: Intercomparisonsmentioning
confidence: 75%
“…This spectral modulation is similar to the background measurement technique used by OH LIF instruments except that for NO 2 there is still appreciable fluorescence at the off-resonance frequency due to the continuum in the absorption spectrum. This technique has been applied in both the stratosphere (Perkins et al, 2001) and the troposphere (Cleary et al, 2002;Fong & Brune, 1997;Matsumoto and Kajii, 2003;Matsumi et al, 2001;Matsumoto et al, 2001;Thornton et al, 2000). In the instrument described in detail by Thornton et al (2000), the output from a narrow linewidth dye laser pumped by a 3 W, 8 kHz Nd:YAG laser excites a pair of overlapping rotational lines in the (430) A 2 B 2 ← 000 X 2 A 1 vibronic band of NO 2 at 17086 5 cm −1 (585.257 nm).…”
Section: Single-photon No 2 Instrument Designmentioning
confidence: 99%
“…As a result, almost simultaneous actinic flux and global irradiance measurements are available at each wavelength from which the polynomials of the SIM method were calculated. The absorption cross section and quantum yield used for the J(O 1 D) calculations were those of Daumont et al (1992) and Matsumi et al (2001) respectively, while for the J(NO 2 ) calculation both functions used were from DeMore et al (1997). For the selection of the cloud free days we used the methodology described in Vasaras et al (2001), which is based on the variability of the measurements from a collocated pyranometer.…”
Section: Ground-based Actinic Flux and Irradiance Measurementsmentioning
confidence: 99%